Anti-angiogenic drug aggravates the degree of anti-resorptive drug-based medication-related osteonecrosis of the jaw by impairing the proliferation and migration function of gingival fibroblasts - Ning Zhao; Qing-xiang Li; Yi-fei Wang; Qiao Qiao; Hong-yuan Huang; Chuan-bin Guo; Yu-xing Guo (BMC, 2023)
Abstract Background Long-term use of anti-resorptive or anti-angiogenic drugs in cancer patients with odontogenic infections may lead to medication-related osteonecrosis of the jaw (MRONJ). This study investigated whether anti-angiogenic agents aggravate MRONJ occurrence in anti-resorptive-treated patients. Methods The clinical stage and jawbone exposure of MRONJ patients caused by different drug regimens were analyzed to ascertain the aggravation effect of anti-angiogenic drugs on anti-resorptive drug-based MRONJ. Next, a periodontitis mice model was established, and tooth extraction was performed after administering anti-resorptive and/or anti-angiogenic drugs; the imaging and histological change of the extraction socket were observed. Moreover, the cell function of gingival fibroblasts was analyzed after the treatment with anti-resorptive and/or anti-angiogenic drugs in order to evaluate their effect on the gingival tissue healing of the extraction socket. Results Patients treated with anti-angiogenic and anti-resorptive drugs had an advanced clinical stage and a bigger proportion of necrotic jawbone exposure compared to patients treated with anti-resorptive drugs alone. In vivo study further indicated a greater loss of mucosa tissue coverage above the tooth extraction in mice treated with sunitinib (Suti) + zoledronate (Zole) group (7/10) vs. Zole group (3/10) and Suti group (1/10). Micro-computed tomography (CT) and histological data showed that the new bone formation in the extraction socket was lower in Suti + Zole and Zole groups vs. Suti and control groups. In vitro data showed that the anti-angiogenic drugs had a stronger inhibitory ability on the proliferation and migration function of gingival fibroblasts than anti-resorptive drugs, and the inhibitory effect was obviously enhanced after combining zoledronate and sunitinib. Conclusion Our findings provided support for a synergistic contribution of anti-angiogenic drugs to anti-resorptive drugs-based MRONJ. Importantly, the present study revealed that anti-angiogenic drugs alone do not induce severe MRONJ but aggravate the degree of MRONJ via the enhanced inhibitory function of gingival fibroblasts based on anti-resorptive drugs.